2020
DOI: 10.1111/ijcp.13895
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of regular insulin adsorption to polypropylene bag and polyvinyl chloride infusion set

Abstract: Aim Clinical application of insulin infusion therapy is usually accomplished with regular human insulin. It is known that the regular insulin adsorbed to the hydrophobic surfaces and different approaches were implemented into the clinical practices. It was aimed to evaluate the rate of adsorption of insulin to polypropylene (PP) bags and polyvinyl chloride (PVC) infusion sets and stability of insulin during the infusion. Methods A 100 IU insulin was added to PP bags containing 100 mL of 0.9% NaCl solution (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Based on the effect and place of action, interactions may be divided into physicochemical interactions, occurring during drug preparation and administration, and pharmacological interactions, which take place in vivo and alter drug action. Reactions between soluble components and interactions with the container are forms of physicochemical incompatibility [35]. Other known interactions between PNA and anticonvulsants are affected by pharmacokinetics, such as the displacement of drugs from their albumin-binding sites, which may have significant consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the effect and place of action, interactions may be divided into physicochemical interactions, occurring during drug preparation and administration, and pharmacological interactions, which take place in vivo and alter drug action. Reactions between soluble components and interactions with the container are forms of physicochemical incompatibility [35]. Other known interactions between PNA and anticonvulsants are affected by pharmacokinetics, such as the displacement of drugs from their albumin-binding sites, which may have significant consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on the differences in infusion containers mainly focuses on drug compatibility (Mohr and Kramer, 2022), and most studies have compared PVC infusion bags with non-PVC infusion bags (Rigge and Jones, 2005). For example, studies have reported that PVC infusion bags have certain adsorption for a variety of drugs, which affects the therapeutic effect; therefore, PVC infusion bags should be avoided for clinical use (Sürmelioğlu et al, 2021). However, there is no difference in drug compatibility between non-PVC infusion bags and upright polypropylene infusion bags (Li H. et al, 2019).…”
Section: Introductionmentioning
confidence: 99%